The impact of corruption on poverty alleviation and economic growth in Tanzania - Mohamed, Mohamed Salum (Graduate School of Management, International Islamic University Malaysia, 2018)
Corruption is one of the major diseases that affects different countries worldwide in different ways. It is a tragedy which threatens both human existence and what they heavily stand for in their survival. Tanzania is one of the countries which has been affected by corruption. Throughout the years it has lost its direction in sustaining its economy and corruption is to blame. This has resulted in the country to suffer as damage has been incurred in all dimensions be it economic, political, financial or social. Unfortunately the effects of corruption have become massive as the level of poverty has been observed to increase significantly. Several studies present issues concerning corruption but between their contexts are very limited, not covering the relationship between corruption with poverty alleviation and economic growth. With that in mind, this study has been designed to investigate the impact of corruption on poverty alleviation and economic growth in Tanzania. The data was collected from 33 respondents: 10 from public officials' category, 10 from businessman/woman category, 10 from household category, and 3 from experts. Economic and governance dimensions were used for the purpose of collecting sufficient data which address the impact of corruption on poverty alleviation and economic growth in Tanzania. From the economic dimensions, the results show that corruption in Tanzania discourages foreign and domestic investments, costs entrepreneurship highly, lowers the quality of public infrastructure, distorts the composition of public expenditure, increases inequality, decreases progressivity of the tax system, decreases tax revenue and targets the social program for the poor. From the governance dimensions, the results show that corruption lowers the quality of the public services, decreases public trust in governance and threatens democracy and governance system in Tanzania. At the end of this study, governance and public awareness remedies have been provided in order to improve the situation in Tanzania. In future studies, the focus can be more specific on different types of corruption in order to understand the root of the problems and to come up with systematic solutions to solve those problems. Finally, the implication of the study is discussed.